## With Safari, you learn the way you learn best. Get unlimited access to videos, live online training, learning paths, books, tutorials, and more.

No credit card required

### Chapter 1

1.1 6 ÷ 2(1+2) = 6 ÷ 2(3) = 3(3) = 9; Note that if you use the standard convention taught in Chapter 1 and multiply and divide in order from left to right, the answer is 9. If you multiply and then divide, you would get 1 because

6 ÷ 2(1+2) = 6 ÷ 2(3) = 6 ÷ 6 = 1;

1.2 12 ÷ 4 + 2·6 - (4 - 3)3 = 12 ÷ 4 + 2·6 -(1)3 = 12 ÷ 4 + 2.6-1 = 3+12 - 1 = 14

1.3 After multiplying the number by 1, the result is the same number; Identity Property of Multiplication

1.4 The order of the addends is reversed; Commutative Property of Addition

1.5 The order of the numbers being multiplied is reversed; Commutative Property of Multiplication

1.6 8(20 + 3) = 8(20) + 8(3) = 160 + 24 = 184

1.7 9(14) + 9(16) = 9(14 + 16) = 9(30) = ...

## With Safari, you learn the way you learn best. Get unlimited access to videos, live online training, learning paths, books, interactive tutorials, and more.

No credit card required